The impact of using blogs and vlogs as an intercultural resource focused on the oral skills in english classes for adults in a community service hours of the sups in the foreign language department of the University of El Salvador in the year 2017. - Arias Hernández, Tatiana Marcela; Ayala Ortiz, Stephanie Yanira; Chicas Masferrer, Morena Guadalupe (2024)
The present research work is based on the study of the impact of using blogs and vlogs as an intercultural resource focused on the oral skills in English classes for adults in a community service hours of the SUPS in the Foreign Language Department of the University of El Salvador in the year 2017. The main objective of this research is to show the impact of the use of blogs and video blogs in the process of learning English as a second language, more than anything by applying these intercultural resources in adult students. Also, to explain what the advantages and disadvantages are when there is no adequate equipment in the classroom. In addition, the methodology selected for this study was qualitative and descriptive method, which means that the research group worked with non-numerical data. Furthermore, it is important to mention that the investigation was carried out with the non-experimental research design, where researchers have complete control over the extraneous variables and can predict confidently that the observed effect on the dependable variable is only due to the manipulation of the independent variable. For the development of this research it was necessary to use instruments such as observation, checklist and questionnaires, which were very helpful at the time of collecting the information and obtaining the necessary results, and completing the investigation.